Antifungal Activity of the Natural Coumarin Scopoletin Against Planktonic Cells and Biofilms From a Multidrug-Resistant Candida tropicalis Strain - Lemos, Ari S. O.; Florêncio, Jônatas R.; Pinto, Nícolas C. C.; Campos, Lara M.; Silva, Thiago P.; Grazul, Richard M.; Pinto, Priscila F.; Tavares, Guilherme D.; Scio, Elita; Apolônio, Ana Carolina M.; Melo, Rossana C. N.; Fabri, Rodrigo L. (Frontiers in Microbiology, 2020)
Candida tropicalis is one the most relevant biofilm-forming fungal species increasingly associated with invasive mucosal candidiasis worldwide. The amplified antifungal resistance supports the necessity for more effective and less toxic treatment, including the use of plant-derived natural products. Scopoletin, a natural coumarin, has shown antifungal properties against plant yeast pathogens. However, the antifungal activity of this coumarin against clinically relevant fungal species such as C. tropicalis remains to be established. Here, we investigated the potential antifungal properties and mechanisms of action of scopoletin against a multidrug-resistant C. tropicalis strain (ATCC 28707). First, scopoletin was isolated by high-performance liquid chromatography from Mitracarpus frigidus, a plant species (family Rubiaceae) distributed throughout South America. Next, scopoletin was tested on C. tropicalis cultivated for 48h in both planktonic and biofilm forms. Fungal planktonic growth inhibition was analyzed by evaluating minimal inhibitory concentration (MIC), time-kill kinetics and cell density whereas the mechanisms of action were investigated with nucleotide leakage, efflux pumps and sorbitol and ergosterol bioassays. Finally, the scopoletin ability to affect C. tropicalis biofilms was evaluated through spectrophotometric and whole slide imaging approaches. In all procedures, fluconazole was used as a positive control. MIC values for scopoletin and fluconazole were 50 μg/L and 250 μg/L respectively, thus demonstrating a fungistatic activity for scopoletin. Scopoletin induced a significant decrease of C. tropicalis growth curves and cell density (91.7% reduction) compared to the growth control. Its action was related to the fungal cell wall, affecting plasma membrane sterols. When associated with fluconazole, scopoletin led to inhibition of efflux pumps at the plasma membrane. Moreover, scopoletin not only inhibited the growth rate of preformed biofilms (68.2% inhibition at MIC value) but also significantly decreased the extent of biofilms growing on the surface of coverslips, preventing the formation of elongated fungal forms. Our data demonstrate, for the first time, that scopoletin act as an effective antifungal phytocompound against a multidrug-resistant strain of C. tropicalis with properties that affect both planktonic and biofilm forms of this pathogen. Thus, the present findings support additional studies for antifungal drug development based on plant isolated-scopoletin to treat candidiasis caused by C. tropicalis.